A dust suppression material with a cross-linked network structure for complex environments and a preparation method thereof

By adopting a high-consolidation-strong weather-resistant cross-linking network structure in dust suppression materials, the problem of poor weather resistance of the cured layer of dust suppression materials in complex climates of open-pit coal mines is solved, and the durable and effective dust suppression effect and good dust suppression effect of dust suppression agents is achieved. environmental adaptability.

CN118460180BActive Publication Date: 2025-02-14SHANDONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410550510.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-02-14
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

The cured layer of dust suppression material in the complex climate of open-pit coal mines has poor weather resistance, resulting in a short-lasting dust suppression effect.

Method used

Based on low viscosity materials, guided by high consolidation-strong weather-resistant crosslinking network structure, it forms a complex environmental crosslinking network structure through crosslinking and oxidation reaction of cassava starch, polyvinyl alcohol, carboxymethyl cellulose and other materials. Dust-repressing material.

Benefits of technology

The water retention and rain corrosion resistance of the cured layer of the dust inhibitor are improved, and can maintain a high-efficiency dust suppression effect in climates such as rain corrosion, high-low temperatures, and are inexpensive and biodegradable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118460180B_ABST
    Figure CN118460180B_ABST
Patent Text Reader

Abstract

The invention discloses a dust suppression material with a complex environment cross-linked network structure and a preparation method thereof, which relates to the technical field of dust control, and comprises 16 to 20 parts of cassava starch, 0.2 to 0.6 parts of polyvinyl alcohol, 0.1 to 0.5 parts of carboxymethyl cellulose, 0.1 to 0.5 parts of a cross-linking agent, 0.24 to 0.28 parts of an oxidant, 0.4 to 0.48 parts of a catalyst, 1.8 to 2.6 parts of a gelatinizer, 0.1 to 0.3 parts of a water retaining agent, 0.8 to 1.2 parts of a wetting agent, and the rest is distilled water. After the dust suppressant prepared by the invention is sprayed on coal dust, it can wet and penetrate into the gaps of coal dust particles, and water molecules form hydrogen bonds with the hydrophilic groups in the cross-linked network structure, and are firmly adsorbed on the network structure, thereby improving the water retention performance of the solidified layer, and the cross-linked network structure makes the coal dust particles agglomerate better, forming a smooth and dense solidified layer, and glycerol can make the solidified layer retain a certain amount of water to prevent the solidified layer from cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dust prevention and control, and in particular to a dust suppression material with a complex environment cross-linked network structure and a preparation method thereof. Background Art

[0002] Coal dust is one of the main disasters in coal mining production. At present, the coal dust pollution problem is an urgent problem to be solved in the world's coal industry. A large amount of dust is generated during coal mining and transportation. The latest environmental pollution monitoring data shows that dust emissions and pollution lead to PM in the surrounding environment. 2.5 and PM 10 The dust seriously exceeds the standard, causing serious harm to the environment. Dust not only seriously threatens the physical and mental health of workers and residents around the mining area, but also causes explosions and coal workers' pneumoconiosis. In addition, since open-pit coal mines are mostly located in dry soil, water-scarce and arid areas, the dust can travel at a speed of more than 3 to 4 m / s, and the PM in the dust can reach 100 to 200 m / s. 2.5 Small particles such as dust are not easy to settle and are blown away by the wind for hundreds of kilometers, further increasing the environmental risks. In addition, the environment of open-pit coal mines is complex. In desertified areas, the temperature in areas directly exposed to the sun can reach over 60°C during the day and the temperature can drop sharply to below -15°C at night, which places high requirements on the freeze-thaw resistance of dust suppressants.

[0003] For the dust control problem in open-pit coal mines, spray technology is one of the most effective methods to suppress dust, but the water after spraying evaporates easily and needs to be re-sprayed in a short time. At present, there are many materials for spray dust suppression, but for the complex open-pit coal mine environment with rain erosion and large temperature changes, the solidified layer of general dust suppression materials has poor tolerance, resulting in a short-lasting dust suppression effect.

[0004] Therefore, there is an urgent need to develop a weather-resistant dust suppression material. Summary of the invention

[0005] In order to solve the technical problem of poor weather resistance of the solidified layer of dust suppression materials under complex climate in open-pit coal mines, the present invention discloses a dust suppression material with a complex environment cross-linked network structure based on a low-viscosity material and guided by a high consolidation-strong weather resistance cross-linked network structure and a preparation method.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a complex environment cross-linked network structure dust suppression material, including cassava starch, polyvinyl alcohol, carboxymethyl cellulose, a cross-linking agent, an oxidant, a catalyst, a gelatinizer, a water retaining agent, a wetting agent, and the rest is distilled water.

[0008] Optionally, a dust suppression material with a complex environment cross-linked network structure comprises the following components in parts by weight:

[0009]

[0010]

[0011] The balance is distilled water.

[0012] Cassava starch is an environmentally friendly natural polysaccharide that is cheap and easily available. Cassava starch is used as a raw material for dust suppression, can provide a skeleton for the cross-linked network, is easily biodegradable, and has good environmental adaptability.

[0013] Polyvinyl alcohol is an organic compound with multiple hydroxyl groups in its chain structure. It has good film-forming properties and biodegradability. Its structure has certain similarities with starch, so it has good compatibility with starch. In order to enhance the curing strength of the dust suppressant, polyvinyl alcohol is combined with other materials to prepare a cross-linked network material.

[0014] Carboxymethyl cellulose has high solubility and high stability, and has high stability in a wide range of temperature and pH, and can be used as a reinforcing agent for dust suppression materials.

[0015] Optionally, the cross-linking agent is glutaraldehyde, the oxidant is hydrogen peroxide, the catalyst is copper sulfate, the gelatinizer is sodium hydroxide, and the water-retaining agent is glycerol.

[0016] Glutaraldehyde is an important cross-linking agent and is widely used in materials, chemical industry and other fields. Glutaraldehyde has good cross-linking effect and stability.

[0017] Copper sulfate is used as a catalyst. The efficiency of metal ion catalysts frequently used in oxidation processes can be ranked as follows: Cu>Fe>WO4.

[0018] Hydrogen peroxide is one of the most common oxidants. It eventually decomposes into oxygen and water during the oxidation process and is environmentally friendly.

[0019] Glycerin, as a water-retaining auxiliary material, can prevent the cured film from drying out and cracking.

[0020] Optionally, the wetting agent is alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside, and the mass ratio of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside is 2:3. Fatty alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside are used as wetting agents. Fatty alcohol polyoxyethylene ether sodium sulfate is an anionic surfactant that is easily soluble in water. Alkyl glycoside has low surface tension, strong wetting ability, and good penetration effect. It is usually compounded with other surfactants to play a synergistic role.

[0021] The second aspect of the present invention provides a method for preparing the above-mentioned dust suppression material, comprising the following steps:

[0022] (1) Add distilled water and cassava starch to a beaker, stir for 10 min to ensure a uniform suspension, add a crosslinker, heat to 50°C, and heat in a water bath for 1 h to obtain a mixed solution I;

[0023] (2) Adding a catalyst and an oxidant to the mixed solution I, mixing thoroughly and then standing for 30 minutes for catalytic oxidation; slowly adding the dissolved gelatinizer to the beaker containing the oxidized cross-linked starch and continuing to stir, and standing for 24 hours to obtain a mixed solution II;

[0024] (3) Add polyvinyl alcohol and distilled water to a beaker, raise the temperature to 95°C, cool until the polyvinyl alcohol is completely dissolved, add the diluted mixed solution II, carboxymethyl cellulose and water retaining agent, mix thoroughly and heat in a water bath for 1 hour to obtain mixed solution III;

[0025] (4) After the mixed solution III is cooled to room temperature, the pH value of the solution is adjusted, and a wetting agent is added to the mixed solution III to obtain a dust suppressant solution with a complex environment cross-linked network structure.

[0026] Optionally, the cross-linking agent is glutaraldehyde, the oxidant is hydrogen peroxide, the catalyst is copper sulfate, the gelatinizer is sodium hydroxide, and the water-retaining agent is glycerol.

[0027] Optionally, the wetting agent is sodium alcohol polyoxyethylene ether sulfate and alkyl glycoside, and the mass ratio of sodium alcohol polyoxyethylene ether sulfate to alkyl glycoside is 2:3.

[0028] Reaction equation of the present invention is as follows:

[0029]

[0030] Starch is represented by St-CH2OH. The starch molecule contains multiple hydroxyl groups. Oxidized cross-linked starch is represented by CLSt-COOH. During the oxidation process, there will be weaker active hydroxyl groups that are not completely oxidized. Therefore, the product of step (3) exists in the form of HO-CLSt-COOH.

[0031] The reaction principle of the present invention is:

[0032] (1) The aldehyde group in the glutaraldehyde molecule undergoes an etherification cross-linking reaction with the hydroxyl group on the cassava starch molecule. The newly generated chemical bonds continuously replace the original hydrogen bonds on the original molecular chain, forming a compact cross-linked network structure of cassava starch.

[0033] (2) The cross-linked cassava starch is oxidized and hydrogenated, which further oxidizes some of the active hydroxyl groups in the cross-linked starch molecules into carboxyl groups. At the same time, the oxidation reaction breaks the glycoside chains, partially degrades the starch molecules, and reduces the molecular weight.

[0034] (3) Oxidized cross-linked starch serves as the skeleton, and polyvinyl alcohol, oxidized cross-linked starch, and carboxymethyl cellulose are connected by hydrogen bonds. The molecular chains are entangled and cross-linked to form an interpenetrating network structure, and finally form a three-dimensional hydrogen bond network structure with water and surfactants.

[0035] A third aspect of the present invention proposes an application of the above-mentioned dust suppression material, which is applied to dust control in complex open-air environments.

[0036] The beneficial effects of the present invention are:

[0037] 1. The present invention adopts a method of first cross-linking and then oxidation to modify cassava starch, thereby avoiding oxidation reaction to consume too many hydroxyls and reducing the degree of cross-linking. The aldehyde groups in the glutaraldehyde molecules react with the hydroxyls on the cassava starch molecules to undergo etherification cross-linking reaction, and the newly generated chemical bonds continuously replace the original hydrogen bonds on the original molecular chains. The generated cassava starch cross-linked network structure is tight, and the cross-linked bonds are firm, thereby increasing the strength and cohesion of the cross-linked cassava starch.

[0038] 2. The cross-linked cassava starch is oxidized by hydrogen peroxide, which further oxidizes some of the active hydroxyl groups in the cross-linked starch molecules into carboxyl groups. At the same time, the oxidation reaction breaks the glycoside chains, reduces the viscosity of the starch, and improves its fluidity and water resistance.

[0039] 3. The modified starch is copolymerized with polyvinyl alcohol and carboxymethyl cellulose, and then compounded with sodium polyoxyethylene fatty alcohol ether sulfate (AES) and alkyl polyglycoside (APG-0810) to finally obtain a low-cost, biodegradable dust suppression material.

[0040] 4. After the dust suppressant prepared by the present invention is sprayed on the coal dust, it can wet and penetrate into the gaps between the coal dust particles. The water molecules form hydrogen bonds with the hydrophilic groups in the cross-linked network structure and are firmly adsorbed on the network structure, thereby improving the water retention performance of the solidified layer. The cross-linked network structure makes the coal dust particles agglomerate better to form a smooth and dense solidified layer. Glycerin can make the solidified layer retain a certain amount of moisture to prevent the solidified layer from cracking.

[0041] 5. The dust suppressant prepared by the present invention can still effectively suppress dust in the solidified layer under the conditions of rain erosion, high-low temperature and other climates. The solidified layer remains intact after being washed and soaked for 24 hours, can adapt to temperature changes of -18 to 60°C, and has a water retention performance that is 40.0% higher than that of water. On the basis of ensuring wetting, the dust suppressant's weather resistance such as high temperature resistance, freeze-thaw resistance, and rain erosion resistance is enhanced, providing a feasible solution for the application of chemical dust suppression in dust control in complex open-air environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The present invention is a flow chart of a preparation method of a dust suppression material with a complex environment cross-linked network structure. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0044] The invention discloses a dust suppression material with a complex environment cross-linked network structure, which is based on a low-viscosity material and guided by a high-consolidation-strong weather-resistant cross-linked network structure. The raw materials used include 16 to 20 parts of cassava starch, 0.2 to 0.6 parts of polyvinyl alcohol, 0.1 to 0.5 parts of carboxymethyl cellulose, 0.1 to 0.5 parts of a cross-linking agent, 0.24 to 0.28 parts of an oxidant, 0.4 to 0.48 parts of a catalyst, 1.8 to 2.6 parts of a gelatinizer, 0.1 to 0.3 parts of a water-retaining agent, 0.8 to 1.2 parts of a wetting agent, and the rest is distilled water.

[0045] Example 1

[0046] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0047] (1) Add 100 ml of distilled water and 16 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.1 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0048] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0049] (3) Add 0.2 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 60°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0050] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0051] Example 2

[0052] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0053] (1) Add 100 ml of distilled water and 16 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.5 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0054] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0055] (3) Add 0.4 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 65°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0056] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0057] Example 3

[0058] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0059] (1) Add 100 ml of distilled water and 16 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.3 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0060] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0061] (3) Add 0.6 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 70°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0062] (4) After the mixed solution III is cooled to room temperature, 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and after stirring and dissolving, a complex environment cross-linked network structure dust suppressant can be obtained.

[0063] Example 4

[0064] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0065] (1) Add 100 ml of distilled water and 18 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.5 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0066] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0067] (3) Add 0.2 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 70°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0068] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0069] Example 5

[0070] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0071] (1) Add 100 ml of distilled water and 18 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.3 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0072] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0073] (3) Add 0.4 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 60°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0074] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0075] Example 6

[0076] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0077] (1) Add 100 ml of distilled water and 18 g of cassava starch to a beaker, stir for 10 min to ensure that the suspension is uniform and avoid agglomeration, then add 0.1 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I;

[0078] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0079] (3) Add 0.6 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 65°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0080] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0081] Example 7

[0082] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0083] (1) Add 100 ml of distilled water and 20 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.3 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0084] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0085] (3) Add 0.2 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 65°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0086] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0087] Example 8

[0088] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0089] (1) Add 100 ml of distilled water and 20 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.1 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0090] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0091] (3) Add 0.4 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 70°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0092] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0093] Example 9

[0094] A method for preparing a dust suppression material with a complex environment cross-linked network structure comprises the following steps:

[0095] (1) Add 100 ml of distilled water and 20 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.5 g of glutaraldehyde, heat to 50 °C and heat in a water bath for 1 h to obtain a mixed solution I.

[0096] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for them to dissolve, then slowly add them to the beaker containing the oxidized cross-linked starch and continue stirring, let stand for 24 h to obtain a mixed solution II;

[0097] (3) Add 0.6 g of polyvinyl alcohol and 95 ml of distilled water to a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool; add 5 ml of the diluted mixed solution II, 0.3 g of carboxymethyl cellulose, and 0.2 g of glycerol, mix thoroughly, heat to 60°C, and heat in a water bath for 1 h to obtain mixed solution III;

[0098] (4) After the mixed solution III is cooled to room temperature, the pH of the solution is adjusted and 1 g of alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside (2:3) are added, and the complex environment cross-linked network structure dust suppressant is obtained after stirring and dissolving.

[0099] Comparative Example 1

[0100] (1) Add 100 ml of distilled water and 18 g of cassava starch to a beaker and stir for 10 min to ensure that the suspension is uniform and avoid agglomeration. Then add 0.3 g of glutaraldehyde and heat to 50 °C in a water bath for 1 h to obtain mixed solution I.

[0101] (2) Add 0.44 g copper sulfate and 0.86 ml hydrogen peroxide to the mixed solution I, mix thoroughly and let stand for 30 min for catalytic oxidation; add 20 ml distilled water and 2 g sodium hydroxide to a beaker, wait for it to dissolve, then slowly add it to the beaker containing the oxidized cross-linked starch and continue stirring. Let it stand for 24 h and then dilute it 10 times. Take the diluted solution, add 1 g sodium alcohol polyoxyethylene ether sulfate and alkyl glucoside (2:3), and stir to dissolve.

[0102] Comparative Example 2

[0103] Add 0.4 g of polyvinyl alcohol and 100 ml of distilled water into a beaker, heat to 95°C until the polyvinyl alcohol is completely dissolved, then cool, add 1 g of sodium polyoxyethylene alcohol ether sulfate and alkyl glycoside (2:3), and stir to dissolve.

[0104] The effects of Examples 1-9 and Comparative Examples 1 and 2 were investigated by testing. The following tests were conducted in accordance with the TB / T3210.1-2020 standard for coal sample preparation, and the coal sample of 200 mesh was screened using a standard sieve. The coal was dried in a drying oven at (50±2)°C for 5 hours to remove moisture, and then taken out and placed at room temperature for 1 hour.

[0105] Test 1

[0106] The following tests were conducted on the freeze-thaw resistance and rain erosion resistance of the complex environment cross-linked network structure dust suppressants prepared in Examples 1-9 and Comparative Examples 1 and 2.

[0107] The test method is as follows: an equal amount of coal powder is placed in multiple culture dishes, and 9 samples of the embodiment and 2 samples of the comparative example of the same mass are spread on the surface of the coal dust. The culture dishes are placed in a drying oven, and the constant temperature is 60°C, and heated for 12 hours; then taken out and placed in a refrigerator for low temperature freezing for 12 hours, and the low temperature is set to -18°C; heating and freezing are repeated three times in succession, and the hardness value obtained after freezing and thawing is compared with the initial value, and the hardness loss rate is calculated.

[0108] Using a rain erosion simulation experimental platform, spray at a distance of 0.5 m from the sample at a spray intensity of 10 ml / s for 3 min. Observe the surface state of the solidified layer. After it dries again, weigh its mass and calculate the mass loss rate.

[0109] The test results are shown in Table 1 below.

[0110] Table 1 Freeze-thaw resistance and rain erosion resistance test

[0111]

[0112] The results of test 1 show that, compared with comparative examples 1 and 2, the temperature change of examples 1-9 has less effect on the hardness of the solidified layer, which indicates that the solidified layer is relatively stable in the temperature change of -18 to 60°C and can meet the requirements of freeze-thaw resistance in a complex open-air environment. After being washed by rain, the mass loss rate of example 5 is only 19.86%, and it still has good dust suppression performance, indicating that the solidified layer has good anti-interference performance and good anti-rain erosion performance.

[0113] Test 2

[0114] The complex environment cross-linked network structure dust suppressants prepared in Examples 1-9 and Comparative Examples 1 and 2 were tested for wettability and water retention.

[0115] The test method is as follows: an equal amount of coal powder is placed in a plurality of culture dishes, and the surface of the coal dust is covered with 9 example samples and 2 comparative example samples of the same mass, and the culture dishes are placed in a vacuum drying oven at 50°C. After 2 hours, the samples are taken out, their masses are weighed, and the cumulative evaporation rate of the dust suppressant is calculated.

[0116] Place the coal cake on the sample stage of the contact angle measuring instrument, adjust the surface to be horizontal, form droplets on the surface of the coal cake to be tested through a syringe, and the droplets contact the surface of the coal cake to be tested, and record the contact angle from 0 to 2s.

[0117] The test results are shown in Table 2 below.

[0118] Table 2 Water retention and wettability test

[0119]

[0120] The results of test 2 are analyzed. The dynamic change of the contact angle shows that the wetting effect of Examples 4, 5, and 7 is good. This is because the viscosity of the material is low and the molecular structure contains hydrophilic groups such as hydroxyl groups, so it shows good wetting performance. After 5 hours of drying, the cumulative evaporation rate of Comparative Examples 1 and 2 is more than 95%, and the dust suppression material of the embodiment forms a dense solidified layer after curing, which can retain a certain amount of moisture and has good water retention performance.

[0121] It can be seen that the present invention can design different ratios to test the freeze-thaw resistance, rain erosion resistance, water retention and wettability of the prepared dust suppression material, so as to judge the actual dust suppression effect of the dust suppression material.

[0122] In summary, the dust suppressant prepared by the present invention can still effectively suppress dust in the solidified layer under the conditions of rain erosion, high-low temperature and other climates, and can solve the technical problem of the intolerance of the solidified layer of dust suppression materials under the complex climate of open-pit coal mines, and has good social benefits and considerable economic benefits.

[0123] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a dust suppression material with a cross-linked network structure for a complex environment, characterized in that: The steps include: (1) Add distilled water and cassava starch to a beaker, stir for 10 min to ensure a uniform suspension, add a crosslinker, heat to 50°C, and heat in a water bath for 1 h to obtain a mixed solution I; (2) Adding a catalyst and an oxidant to the mixed solution I, mixing thoroughly and then standing for 30 minutes for catalytic oxidation; slowly adding the dissolved gelatinizer to the beaker containing the oxidized cross-linked starch and continuing to stir, and standing for 24 hours to obtain a mixed solution II; (3) Add polyvinyl alcohol and distilled water to a beaker, raise the temperature to 95°C, cool until the polyvinyl alcohol is completely dissolved, add the diluted mixed solution II, carboxymethyl cellulose and water retaining agent, mix thoroughly and heat in a water bath for 1 hour to obtain mixed solution III; (4) cooling the mixed solution III to room temperature and adjusting the pH of the solution, adding a wetting agent to the mixed solution III to obtain a dust suppressant solution with a complex environment cross-linked network structure; The dust suppression material with a complex environment cross-linked network structure comprises cassava starch, polyvinyl alcohol, carboxymethyl cellulose, a cross-linking agent, an oxidant, a catalyst, a gelatinizer, a water retaining agent, a wetting agent, and distilled water; the weight proportions of the components are as follows: 16-20 parts of tapioca starch Polyvinyl alcohol 0.2-0.6 parts Carboxymethyl cellulose 0.1-0.5 parts Crosslinking agent 0.1~0.5 parts Oxidant 0.24~0.28 parts Catalyst 0.4~0.48 parts 1.8-2.6 parts of gelatinizer Water-retaining agent 0.1~0.3 parts Wetting agent 0.8-1.2 parts; The cross-linking agent is glutaraldehyde, the oxidant is hydrogen peroxide, the catalyst is copper sulfate, the gelatinizing agent is sodium hydroxide, and the water-retaining agent is glycerol; The wetting agents are alcohol polyoxyethylene ether sodium sulfate and alkyl glycoside, and the mass ratio of alcohol polyoxyethylene ether sodium sulfate to alkyl glycoside is 2:

3.

2. An application of the dust suppression material according to claim 1, characterized in that: Applied to dust control in complex open-air environments.

Citation Information

Patent Citations

  • Stockyard dust emission inhibitor as well as preparation method and application thereof

    CN106479277A